A computational parametric analysis of cavitating flows in injector nozzles. (2nd October 2017) - Andrić, Jelena
Abstract: The fuel injection system in diesel engines has crucial influence on the engine's combustion process and emission formation. Cavitation in injector nozzles plays a critical role in primary spray break-up and atomization. Understanding the phenomenon of cavitation is hence important for accurate design of the injection process. This work presents a computational study of the characteristics of cavitating flows in the two-dimensional (2D) injector nozzle. The computations are performed by employing the multi-phase mixture approach with the k–ε realizable turbulence model and Schnerr–Sauer cavitation model. The results demonstrate the capability of the modeling framework to successfully predict the following experimentally observed cavitation regimes: no cavitation, developing cavitation, and super cavitation. A parametric study of the effects of the cavitation number σ and the Reynolds number Re verifies the experimental finding that cavitation strongly depends on σ, while the effect of Re is not large.